Analysis of Purchase Decision Model Towards Airlines Ticket Booking in Traveloka (Mercu Buana Univercity Case Study) - Prapatantio Teteg Pringgodigdoyo; Adi Nurmahdi (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
Traveloka is an airline ticket purchase application that has the most visitors in Southeast Asia, but starting in the first quarter of 2019 they experienced a decline in the number of visitors. The decline in the number of visitors was the most contributed by application users from Indonesia. The decline in the number of visitors is a phenomenon that needs attention because it can potentially affect ticket sales through the application. there are several factors that influence the pattern of ticket purchases through online applications, including internet knowledge, service quality, prices, trust, understanding of risk, and user perceptions.  The objectives in this study is to determine the effect of price, service quality, brand image on purchase decisions on the Traveloka application. The samples of this study are a 100 post graduate students of Mercu Buana University. The results of this study show that price does not have a positive and significant effect on brand image on the Traveloka application. Price, service quality and brand image have a positive and significant influence on purchase decisions on the Traveloka application. Traveloka companies are advised to increase their responsiveness in providing quality services so that they will be able to create a better brand image. Keywords: price, service quality, brand image, purchase decision, traveloka